Penerapan Restorative justice Dalam Tindak Pidana Pelanggaran Lalu Lintas - Akbar, Zainul (Jurnal Litigasi Amsir, 2023)
This research was carried out aiming to find out the factors that impede the implementation of Restorative justice by the Enrekang Resort Police in the settlement of Traffic Crimes. And to find out the application of Restorative justice by the police in the settlement of traffic crimes. The type of research used in this research is normative law research and empirical research. The results of the study show that the settlement of traffic accidents using a Restorative Justice or ADR approach in the jurisdiction of the Enrekang Police has been running for traffic accidents caused by minor injuries. Settlement of traffic accidents through a Restorative justice legal approach can be carried out by means of ADR (Alternative Dispute Resolution) if the accident is in the Mild category. However, if there is a serious accident, Restorative justice cannot be used. Settlement of traffic accident cases using Restorative justice so that there is no accumulation of traffic accident cases. The obstacle that is often faced by investigators from the Traffic Accident Unit of the Enrekang Police in handling traffic accidents with a Restorative Justice approach is only a lack of understanding by some people about Law Number. 22 of 2009. Some people still think that it is the party who is injured or who crashes is the wrong party and Accidents involving Cars and Bicycles, Motorcycles, which are wrong are Cars or Motorcycles and pedestrians, which are wrong are motorcycles.